Pericardial immunoglobulin G4‐related inflammatory pseudotumor after right upper lobectomy for lung cancer. Issue 10 (26th August 2020) - Oda, Risa; Okuda, Katsuhiro; Murase, Takayuki; Sakane, Tadashi; Tatematsu, Tsutomu; Yokota, Keisuke; Endo, Katsuhiko; Nakanishi, Ryoichi
Abstract : A 75‐year‐old woman underwent thoracoscopic right upper lobectomy for lung cancer. A histopathological examination showed adenocarcinoma, pT1aN0M0 stage IA1. At six months after surgery, chest computed tomography (CT) revealed pericardial nodules that had not been detected before pulmonary resection. Postoperative CT performed two months later revealed that the nodules were growing and F 18 fluorodeoxyglucose‐positron emission tomography showed a maximum standardized uptake of 9.87. Blood tests revealed no elevated tumor markers, with the exception of a mildly elevated interleukin‐2. Based on the above results, thoracoscopic biopsy was performed due to the suspected recurrence of lung cancer or malignant lymphoma. The histopathological examination of the nodule revealed immunoglobulin G4 (IgG4)‐related inflammatory pseudotumor. The serum IgG4 levels were elevated (358 mg/dL, normal: 4.5–117.0 mg/dL). No additional treatment was required because all nodules were observed to have disappeared naturally on a follow‐up CT scan performed two months after the surgical biopsy. The patient has been followed‐up for two years without recurrence. Key points: Significant findings of the study: We report a case of pericardial immunoglobulin G4‐related inflammatory pseudotumor that appeared after right upper lobectomy for lung cancer, and which naturally disappeared without any treatment. What this study adds: There was an immunoglobulin G4‐related inflammatory pseudotumor which appeared as multiple nodules in the pericardial space, and this should be kept in mind when considering the differential diagnosis of intrapericardial nodules. Abstract : We report a case of pericardial immunoglobulin G4‐related inflammatory pseudotumor that appeared after right upper lobectomy for lung cancer, and which naturally disappeared without any treatment.